2008
DOI: 10.1007/s12011-008-8211-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Dose Zinc Supplementation to Serum Estrogen and Progesterone Levels in Post-menopausal Women

Abstract: The objective of the present study is to investigate how low-dose zinc supplementation for 2 weeks in the post-menopausal period influences levels of estrogen and progesterone in the serum. The study registered 32 natural menopause patients, who were allocated to four groups with equal number of patients. Group 1, control group, which was not subjected to any procedure. Group 2, the group that was supplemented with 15 mg/day zinc sulfate for 2 weeks. Group 3, the group that was given hormone replacement therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Studies have shown that zinc deficiency in female animals increases the mortality rate of fetuses and results in low pregnancy rates, meaning that zinc deficiency affects reproductive outcomes in mice [11,12]. The study confirmed the preventive effectiveness of zinc in reducing the overall complication rate for both mother and fetus and that diets deficient in zinc are the cause of a high incidence of miscarriage [13]. As well as the role of the ginseng plant, the results of the current study showed that it has beneficial effects on the reproductive performance of local ewes.…”
Section: Pregnancy Progesterone Concentrationsupporting
confidence: 58%
“…Studies have shown that zinc deficiency in female animals increases the mortality rate of fetuses and results in low pregnancy rates, meaning that zinc deficiency affects reproductive outcomes in mice [11,12]. The study confirmed the preventive effectiveness of zinc in reducing the overall complication rate for both mother and fetus and that diets deficient in zinc are the cause of a high incidence of miscarriage [13]. As well as the role of the ginseng plant, the results of the current study showed that it has beneficial effects on the reproductive performance of local ewes.…”
Section: Pregnancy Progesterone Concentrationsupporting
confidence: 58%
“…Since progestin had little ability to reverse OHT and ICI inhibition of T47D cell growth, the progestin effect is likely related to the ERαY537S and ERαD538G mutations. Consistent with the possibility that serum progestin might influence antiestrogen resistance in women whose breast cancers express the ERαY537S and ERαD538G mutations, progesterone levels in post-menopausal women are 0.6–3 nM 59 60 61 . Moreover, breast cancer cells expressing both ERα and PR, or overexpressing PR alone, may be sensitive to very low concentrations of hormone 17 18 .…”
Section: Discussionmentioning
confidence: 73%
“…However, relevant reports on the relationship between zinc and PRG are not without controversy. One report determined that two weeks’ supplementation with low-dose zinc had no significant effect on serum estradiol and PRG concentration in postmenopausal women [ 80 ]. Another report suggested that zinc may play an inhibitory role in the onset and maintenance of PRG production in a mouse study.…”
Section: Zinc and The Cmpn/cmp Signaling Networkmentioning
confidence: 99%